2014
DOI: 10.32614/rj-2014-031
|View full text |Cite
|
Sign up to set email alerts
|

MVN: An R Package for Assessing Multivariate Normality

Abstract: Assessing the assumption of multivariate normality is required by many parametric multivariate statistical methods, such as MANOVA, linear discriminant analysis, principal component analysis, canonical correlation, etc. It is important to assess multivariate normality in order to proceed with such statistical methods. There are many analytical methods proposed for checking multivariate normality. However, deciding which method to use is a challenging process, since each method may give different results under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
605
0
47

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,012 publications
(653 citation statements)
references
References 21 publications
1
605
0
47
Order By: Relevance
“…residuals, which is the magnitude of difference between estimated age and chronological age. The response variable was symmetrically distributed among comparison groups, however; statistical tests rejected normality as a result of large sample size [36,37]. Previous studies showed that ANOVA is robust to moderate departures from normality and can be used when sample size is large enough [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…residuals, which is the magnitude of difference between estimated age and chronological age. The response variable was symmetrically distributed among comparison groups, however; statistical tests rejected normality as a result of large sample size [36,37]. Previous studies showed that ANOVA is robust to moderate departures from normality and can be used when sample size is large enough [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate outlier detection was done based on robust Mahalanobis distance. All analyses were carried out using the R language and environment for statistical graphics and computing63, and associated packages ( MVN v.4.064 and car 65). Strength of shift in MSP amounts was calculated as standardized mean differences.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the multivariate outliers were graphically checked by the QQPlot (''chisplott'' function) for the observed Mahalanobis distances. Bartlett's test was used to test the homogeneity of variance (homoscedasticity), while either univariate and multivariate normality were performed with the Shapiro-Wilk and Mardia skewness tests (''MVN'' R package by Korkmaz et al 2014), respectively. In order to investigate which variables account for differences among ADR classes, univariate ANOVA tests were also performed.…”
Section: Resultsmentioning
confidence: 99%